2017
DOI: 10.1002/pi.5473
|View full text |Cite
|
Sign up to set email alerts
|

One-pot synthesis of {Mo6 I8 }4+ -doped polystyrene microspheres via a free radical dispersion copolymerisation reaction

Abstract: Molybdenum octahedral clusters, when incorporated into an appropriate polymer matrix, are considered as promising agents for a range of biological applications. This work describes the one-pot synthesis, morphology and cellular toxicity of nano-sized polystyrene beads doped with luminescent cluster complexes [{Mo 6 X 8 }(NO 3 ) 6 ] 2− (X = Cl, Br or I). Specifically, the particles were obtained by free radical dispersion copolymerisation of styrene and methacrylic acid or 4-vinylpyridine in the presence of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 53 publications
0
8
0
Order By: Relevance
“…(1-trimethylsilyl-1-propyne), 19 polyurethane, 12,20 silicone, 21,22 amorphous carbon, 23 polymethylmethacrylate, [24][25][26][27] poly(D,L-lactide-co-glycolide), 28 polymeric hydrogel nanoparticles 29 polystyrene, [30][31][32][33][34][35] SiO2 8, [36][37][38][39][40] and ZnO. 8,41 Some of these materials have proved useful for technological applications such as solid state emission, 8, 25,41 oxygen sensing, 19,20 time-gated bioimaging, 39 photochemical oxygenations 2,31,33,34,37 and photodynamic therapy (both anticancer 28,38,40,42 and antibacterial 31,34 ).…”
mentioning
confidence: 99%
“…(1-trimethylsilyl-1-propyne), 19 polyurethane, 12,20 silicone, 21,22 amorphous carbon, 23 polymethylmethacrylate, [24][25][26][27] poly(D,L-lactide-co-glycolide), 28 polymeric hydrogel nanoparticles 29 polystyrene, [30][31][32][33][34][35] SiO2 8, [36][37][38][39][40] and ZnO. 8,41 Some of these materials have proved useful for technological applications such as solid state emission, 8, 25,41 oxygen sensing, 19,20 time-gated bioimaging, 39 photochemical oxygenations 2,31,33,34,37 and photodynamic therapy (both anticancer 28,38,40,42 and antibacterial 31,34 ).…”
mentioning
confidence: 99%
“…S1), as a particularly handy precursor for a range of luminescent materials. [33][34][35][36][37] Specifically, we showed that red emitting mono-disperse SNPs and SMPs that have sizes of 50 nm and 500 nm, respectively, can be easily prepared via slightly modified Stöber process in a one-step reaction. 35 In this process tetraethyl orthosilicate (TEOS) is hydrolysed by ammonia in the presence of the cluster.…”
Section: Introductionmentioning
confidence: 99%
“…On the basis of our broad experience with octahedral transition-metal cluster complexes, particularly, molybdenum clusters [{Mo 6 X 8 }­L 6 ] n (X = Cl, Br, or I; L = organic or inorganic ligands; Figure ), we suggest considering them as promising agents for photocatalytic water purification. Their variable terminal ligand (L) environment provides for chemical reactivity and solubility, while the highly stable cluster core {Mo 6 X 8 } 4+ is responsible for the photophysical properties, i.e., photoluminescence and the ability to generate reactive oxygen species (ROS), such as singlet oxygen, hydroxyl radical, superoxide radical, etc. ,, Owing to these beneficial characteristics, this class of compounds is already well-studied for numerous applications, including as components of optical waveguides, liquid-crystal devices, solar panels, antibacterial materials, , agents for bioimaging , and photodynamic therapy, ,,,, and catalysts. However, the water treatment processes employing hexamolybdenum cluster complexes remain little explored.…”
Section: Introductionmentioning
confidence: 99%
“…However, a simple two-component system containing a cluster and a support for heterogeneous photocatalysis has not been described. At the same time, cluster complexes have been often combined with various matrixes beyond graphene oxide, ,, such as MIL-101 9 and SiO 2 meso- and nanoparticles, ,, polystyrene, ,,,,, polyurethane, poly­(methyl methacrylate), , and poly­(vinylpyrrolidone) …”
Section: Introductionmentioning
confidence: 99%